2011
DOI: 10.1099/jmm.0.028126-0
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community and metabolomic comparison of irritable bowel syndrome faeces

Abstract: Human health relies on the composition of microbiota in an individual’s gut and the synthesized metabolites that may alter the gut environment. Gut microbiota and faecal metabolites are involved in several gastrointestinal diseases. In this study, 16S rRNA-specific denaturing gradient gel electrophoresis and quantitative PCR analysis showed that the mean similarity of total bacteria was significantly different (P<0.001) in faecal samples from patients with irritable bowel syndrome (IBS; n = 11) and from non-IB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
157
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(164 citation statements)
references
References 39 publications
5
157
1
1
Order By: Relevance
“…IBS is characterized by abdominal pain or discomfort and altered bowel habits. Although the aetiology is multifactorial, recent understanding of the pathophysiology of IBS has revealed that variations in the normal gut microbiota may have a role to play in the low-grade intestinal inflammation associated with the syndrome [Brint et al 2011;Ponnusamy et al 2011]. Microbial dysbiosis in the gut is thought to be involved in IBS pathogenesis through facilitating adhesion of pathogens to the bowel wall (for a review, see Ghoshal and colleagues [Ghoshal et al 2012]).…”
Section: Irritable Bowel Syndromementioning
confidence: 99%
“…IBS is characterized by abdominal pain or discomfort and altered bowel habits. Although the aetiology is multifactorial, recent understanding of the pathophysiology of IBS has revealed that variations in the normal gut microbiota may have a role to play in the low-grade intestinal inflammation associated with the syndrome [Brint et al 2011;Ponnusamy et al 2011]. Microbial dysbiosis in the gut is thought to be involved in IBS pathogenesis through facilitating adhesion of pathogens to the bowel wall (for a review, see Ghoshal and colleagues [Ghoshal et al 2012]).…”
Section: Irritable Bowel Syndromementioning
confidence: 99%
“…Soil DNA was extracted using a commercial kit (Power Soil TM DNA Isolation Kit, Mo-BIO Laboratories, Inc., Carlsbad, CA, USA) according to the manufacturer's instructions. The V3 region of the 16S ribosomal RNA gene of the soil bacterial community was amplified using universal primers GC341F (341F with a GC clamp) and 907R (Ponnusamy et al 2011) using a Takara Ex Taq TM polymerase kit (Takara Bio Inc., Otsu, Japan). A DNA quantity of between 0.7 and 2.1 ng was used as the template DNA.…”
Section: Soil Sampling and Physicochemical Profilingmentioning
confidence: 99%
“…For clarity, these studies are represented under a separate sub-heading in Table 1. Besides differing from control subjects, IBS also differs from IBD including Crohn's disease and ulcerative colitis (Enck et al, 2009;Ponnusamy et al, 2011).…”
Section: Gut Microbiota In Ibsmentioning
confidence: 99%
“…Compared to non-IBS controls, subjects with IBS have been associated with a greater temporal instability of the GI microbiota and quantitative changes have been detected within several distinct bacterial groups or species-like phylotypes, which are defined based solely on sequence data (see Table 1 for references). In analyses covering the overall microbial community, IBS subjects have shown a tendency to cluster apart from the healthy control subjects (Ponnusamy et al, 2011;Rajilić-Stojanović, 2007). Moreover, the IBS symptom-subgroups IBS have been proposed to differ from each other according to the GI microbiota of subjects within these groups Malinen et al, 2005;RajilicStojanovic, 2007).…”
Section: Introductionmentioning
confidence: 99%